An Evaluation of reading Comprehension Tasks in English 12 Regarding Literal and Inferential Comprehension Tasks = Đánh giá các bài tập đọc hiểu trong sách tiếng Anh 12 dựa trên các bài tập nghĩa đen và nghĩa suy luận. M.A Thesis Linguistics: 60 140 111 - Lê, Thị Dung (University of Languages and International Studies, 2017)
68 p. + CD-ROM